The gut–kidney axis in chronic kidney disease: mechanisms, microbial metabolites, and microbiome-targeted therapeutics - Alobaidi, Sami (Frontiers in Medicine, 2025)
Chronic kidney disease (CKD) remains a major global health issue, affecting millions and presenting persistent diagnostic and therapeutic challenges. Conventional biomarkers such as serum creatinine and estimated glomerular filtration rate have well-recognized limitations, underscoring the need for novel diagnostic tools and interventions. Emerging evidence highlights the gut–kidney axis as a central contributor to CKD pathogenesis, shaped by microbial dysbiosis and altered metabolite production. Harmful metabolites such as indoxyl sulfate, p-cresyl sulfate, and trimethylamine-N-oxide promote inflammation, endothelial dysfunction, and fibrosis, while loss of protective short-chain fatty acids impairs barrier integrity and immune regulation. This review integrates mechanistic, translational, clinical, and therapeutic perspectives, offering a comprehensive and distinctive synthesis of current knowledge. We emphasize both harmful and protective microbial metabolites, incorporate the often-overlooked oral–gut–kidney axis, and highlight advances in multi-omics and computational approaches for biomarker discovery. Microbiome-targeted interventions—including dietary strategies, prebiotics, probiotics, synbiotics, oral adsorbents, and fecal microbiota transplantation—are critically evaluated with respect to efficacy, safety, and translational readiness. By bridging basic science, clinical evidence, and therapeutic implications, this review provides a forward-looking framework for integrating microbiome insights into CKD diagnosis and management. Our synthesis complements existing literature while highlighting unmet needs, thereby informing future research priorities and guiding the development of clinically relevant microbiome-based strategies.